Fingerprint localization algorithm based on linear spatial dependence of WLAN RSS - Xiaoliang XU; Jian GAO; He HUANG; Zhe MA (Dianxin kexue)
Due to RSS time-varying and difference of signal receiving ability of different terminals,the performance of RSS-based technologies is usually instability.In order to solve such problem, a novel fingerprint localization algorithm based on linear spatial dependence of RSS was proposed.Multiple sets of RSS samples were collected at each reference point to form a feature matrix and an offline location fingerprint database was conducted.When the real-time RSS matrix was used to calculate the correlation between the real-time RSS matrix and the reference point of the fingerprint library, the k-reference points were obtained, and the final position of the user was calculated by the quadratic weighted centroid algorithm.In order to effectively reduce the influence of signal time-varying,the sampling and sorting process were carried out, and the number of sampling times increased as much as possible when constructing the offline fingerprint database,but the samples needed to be aggregated to fit the positioning correlation calculation.Experiment results show that the proposed algorithm can guarantee the high positioning accuracy and also achieve the better stability for different terminal.